The Social Significance and Implications of the Ekpe Shrine in Calabar, Nigeria - Offiong Offiong , Asuquo (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
A shrine is a building or place that is hallowed, venerated or deeply respected. It is generally associated with divinities or deities where sacrifices or offerings are made to them. Their devotees often meet there, interact with each other and consult with the priests of the divinities. There is an element of mystery and awe associated with every shrine. Non devotees have little or no business at a shrine, while the devotees themselves have to be very careful and observe various laws while a shrine. Shrines are common in Calabar, and its environs in Nigeria. There is virtually none, dedicated to the Supreme Being, rather they are dedicated to local, deities and secret cults, where a lot of social activities are performed. One of such cult is the Ekpe society shrine which has both social and religious aspects and implications. This paper examines the social significance and implications of the Ekpe shrines in Calabar, and suggests ways in which they could be utilized for the benefit of the community today.